Resolution of Land Disputes in Tourism Development in Bali With an Administrative Law Approach and Restorative Justice Based on Local Wisdom - Nengah Sujana (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2025)
Land disputes in Bali in tourism development reflect multidimensional challenges involving legal, social, cultural and economic, especially related to tensions between customary rights of indigenous communities and formal regulations. This research analyzes dispute resolution through an administrative law approach and restorative justice based on local wisdom. Using the normative juridical method, research shows that although administrative law plays a strategic role in land management, its implementation is often hampered by transparency and maladministration. On the other hand, approach restorative justice, which prioritizes dialogue and deliberation, effectively creating agreements, supported by local values such as Tri Hita Karana. The case study in the Kuta Traditional Village emphasizes the importance of integrating formal law with local wisdom in mitigating conflict and ensuring justice for indigenous communities. The recommendation of this research is the harmonization of administrative law with customary law through regulations that are more sensitive to local values to strengthen the rights of indigenous peoples and support inclusive and sustainable tourism development.